The Adverse Effects of Social Media on Women: A Case Study of Risks and Harmful Impacts - Fatana Dayan; Nazila Samadi; Nooria Nazari; Diba Khalil; Sonia Arsalan (Tinta Emas Institute, 2024)
This study examines the adverse effects of social media on women's mental health, body image, and overall well-being. Utilizing a quantitative research methodology, a survey was conducted among 150 students from four faculties at an online university, focusing on their social media usage patterns and perceptions. The purpose of this research is to investigate how engagement with social media influences women’s self-esteem, body image concerns, and experiences of cyberbullying. Data analysis was performed using Excel to derive frequency distributions and percentages, revealing that a significant proportion of respondents reported negative impacts related to social media use. Results indicated that 40% of participants felt their social media usage contributed to negative body image perceptions, while 26.67% experienced cyberbullying or harassment at least sometimes. These findings underscore the complex interplay between social media engagement and women's mental health, suggesting a need for interventions to mitigate these adverse effects. In conclusion, while social media provides avenues for connection, it also poses significant risks that require attention from educators and policymakers. The study highlights the importance of promoting digital literacy and resilience among female users to navigate these challenges effectively.